(untitled) (Dialogos, 2018)
Resumo. O artigo quer levantar pressupostos de uma leitura da história colonial da Educação. Aborda o que seja história, o trabalho do historiador, história colonial, discutindo categorias como subjetividade, totalidade, forma de ser, sociedade. Faz confronto entre as posições assumidas e as expostas por Fernando de Azevedo em A Cultura Brasileira, insistindo na concepção de sociedade e na função das letras. Conclui com considerações sobre fontes e documentos. Abstract. This article wants to put forward what is necessary for the understanding of the colonial History of Education. It deals with what is meant by History, by the work of the historians, and by colonial History, and discusses categories like subjectivity, totality, forms of being, and society. It confronts the positions assumed by the author against those exposed by Fernando de Azevedo in “A Cultura Brasileira”, insisting on a conception of society and on the role of the school. It concludes with considerations about sources and documents.